Management of Developmental and Epileptic Encephalopathies - Vasquez, Alejandra; Fine, Anthony L. (Seminars in Neurology, 2025)
Developmental and epileptic encephalopathies (DEEs) are a group of rare, severe, early-onset epilepsies characterized by pharmacoresistance, marked electroencephalographic abnormalities, and delayed or regressive psychomotor development. DEEs are associated with poor long-term outcomes and increased mortality; however, early recognition and targeted treatment can impact neurodevelopmental outcomes and overall quality of life. Treatment with antiseizure medication is often challenging given drug resistance, chronic polypharmacy, and medication interactions. With advances in genetic testing and increased understanding of the neurobiological mechanisms of DEEs, the treatment approach is evolving and includes repurposed antiseizure medications and targeted therapies, as well as early surgical intervention in select patients. In addition to high seizure burden and neurodevelopmental delay, DEEs are associated with comorbidities affecting a range of body systems; these can include intellectual disability, psychiatric disorders, motor dysfunction, and respiratory and gastrointestinal problems. Over time, these comorbidities increase the complexity of management and have important implications on the disease burden and quality of life for both patients and their caregivers. Multidisciplinary care in DEEs is paramount. We summarize the current evidence on the management of specific DEEs, focusing on targeted therapies and optimizing outcomes.
Keywords: developmental and epileptic encephalopathy; intractable epilepsy; management; comorbidities; therapies